Rancang Bangun Sistem Deteksi Pergerakan Kepala pada Pemilihan Enam Menu Makanan menggunakan Metode Optical Flow berbasis NVIDIA Jetson Nano - Huda Ahmad Hidayatullah; Fitri Utaminingrum (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Covid-19, known as the corona virus, is a zoonotic disease that is transmitted from animals to humans through viruses in the form of droplets and aerosols. And in 2020, the director general of the World Health Organization (WHO) Tedros Adhanom Ghebreyesus has announced that COVID-19 has become the official name of the corona virus that originated in Wuhan, China (WHO, 2020). And also announced that the risk of transmission through air and touch can be much higher in places that are bad at regulating health rules and protocols, such as restaurants, canteens, and food courts in malls and so on. Where many people spend a long period of time. Therefore, this study aims to help efforts to break the chain of the spread of the Covid-19 virus by implementing a minimal touch or touchless device system in public facilities that require direct contact with devices such as electronic keyboard-mouse, remote control or also in choosing a device. menu display with LCD screen. In this study, a head movement detection system was applied to the selection of six food menus using the Nvidia Jetson Nano- based optical flow method. The study was conducted to determine the effectiveness of the average accuracy in the study and it was obtained that 85.7% at a combination of distances at 45 cm, 55 cm, and 65 cm with an average computation time of 0.040861 s in the combination Head movement turned to the right, to the left, up and down..